Combined surgical and orthodontic treatment of impacted second lower premolar: Case report - Simić Ivana; Domazet Tanja; Lečić Jelena; Ješić Jelena (Serbian Medical Society - Dental Section, Belgrade, 2017)
Impacted tooth is a tooth that has failed to reach occlusal plane, with 2/3 of completed root growth. There are various reasons for teeth impaction, however, lack of space for its emergence is considered to be the main reason. The most commonly impacted teeth are lower wisdom teeth, then upper wisdom teeth, upper canines, and less frequently lower premolars. There are only few studies that have addressed the issue of impacted lower premolars, their etiology, prevalence and treatment. The patient (22 years old) visited orthodontst for the lower jaw aesthetic teeth corrections, due to crowding. Ortopantomography analysis revealed impacted lower right second premolar that caused resorption of mesial root of the first molar. The treatment plan included tooth #46 extraction and placing orthodontic brackets on the impacted second premolar. The next step was extrusion of the tooth #45, its introduction to occlusal plane and orthodontic treatment resumption. Orthodontic treatment of impacted teeth with fixed orthodontic appliance provides excellent therapeutic results. The treatment success depends primarily on adequate planning, cooperation and joint work of oral surgery and orthodontic specialists.